Practical teaching in emergency medicine - Rogers, Robert L.; Mattu, Amal. (Chichester, West Sussex : John Wiley & Sons, 2012)
"Emergency medicine attendings who wish to hone their teaching skills can find a number of books on educational strategies written by physicians from other disciplines. However, until the publication of the first edition of this book, they did not have access to a text written by emergency medicine physicians on methods of teaching that are directly applicable to teaching EM. This book was compiled to meet that need. Following the introductory section, which provides important background information, the book's contents are organized into 4 sections that correspond to the core needs and interests of EM educators: Section 2 focuses on practical and ethical considerations of teaching in the ED; Section 3 provides strategies for teaching specific groups of learners; Section 4 looks at the skills that are characteristic of the best EM educators; and Section 5 looks indepthly at specific teaching techniques and strategies. Now more than ever this book addresses the needs of physician educators from all over the world. New chapters discuss lecturing to an international audience; using simulation as a teaching tool; how to make journal club work for you, and other topics that are of broad interest to medical educators in this field. In general, each chapter has been updated and reviewed to make sure the content was something that emergency physician educators could use in any country .The chapter contributors are widely regarded as leaders in the field of emergency medicine education and faculty development. Authors were given free rein to develop their chapters and write in their own style. They were asked to present their personal views on how to successfully teach the art of emergency medicine, rather than review evidence-based guidelines regarding medical education. As a result, most of the chapters have few references. This first-person approach to a multi-authored textbook yields a compilation that varies in style from chapter to chapter and exposes the reader to a variety of communication techniques"--Provided by publisher.
Machine generated contents note: Section 1. Background/introduction -- 1. Adult learners in the emergency department / Ellen J. O'Connell and Kurt C. Kleinschmidt -- 2. Obstacles to teaching in the emergency department / David K. Duong, Esther K. Choo, and Jeffrey A. Tabas -- 3. Teaching and patient care in emergency medicine / Michael A. Bohrn and David A. Kramer -- 4. Mentoring in emergency medicine / Gus M. Garmel -- Section 2. Teaching in the emergency department and beyond -- 5. Bedside teaching in the emergency department / Kevin G. Rodgers -- 6. Teaching invasive medical procedures / Siamak Moayedi and Mercedes Torres -- 7. Providing feedback in the emergency department / David A. Wald -- 8. The computer as a teaching tool / Joshua S. Broder -- 9. Educational technology : web 2.0 / Michael C. Bond and Robert Cooney -- 10. Teaching the intangibles : professionalism and interpersonal skills/communication / David K. Zich and James G. Adams -- 11. Teaching lifelong learning skills : journal club and beyond / Christopher R. Carpenter -- 12. Medical podcasting 101 / Scott D. Weingart and Robert Orman -- 13. Use of simulation in emergency department education/ Traci L. Thoureen and Sara B. Scott -- Section 3. Teaching specific groups -- 14. Teaching medical students / David E. Manthey -- 15. Teaching residents from other services in the emergency department / Michelle Lin and Amer Z. Aldeen -- 16. The education of resident physicians in emergency medicine / Jonathan G. Wagner, William K. Mallon, and Stuart P. Swadron -- 17. Teaching residents how to teach / Carey D. Chisholm -- 18. Teaching to an international audience / Terrence M. Mulligan -- 19. The emergency department consultation : teaching physician-physician communication to improve patient outcomes / Chad S. Kessler, Yalda Afshar, and Albert C. Vien -- Section 4. Improving as an educator in emergency medicine -- 20. Characteristics of great teachers / Jennifer Avegno and Peter M.C. DeBlieux -- 21. Effective presentation skills / Joseph R. Lex, Jr. and Zachary Repanshek -- 22. Small-group discussion skills / Matthew D. Deibel and Mary Jo Wagner -- 23. Faculty development as a guide for becoming a better teacher / Gloria J. Kuhn -- Section 5. Teaching techniques and strategies -- 24. Strategies for effective clinical emergency department teaching / Glen W. Bandiera and Shirley Lee -- 25. Pearls and pitfalls in teaching / Brian Clyne and David G. Lindquist.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Emergency medicine -- Study and teaching; Emergency Medicine -- education; Emergency Service, Hospital; Teaching; MEDICAL -- Allied Health Services -- Emergency Medical Services; MEDICAL -- Emergency Medicine; MEDICAL -- Nursing -- Emergency; Emergency medicine -- Study and teaching; Electronic books